PENGEMBANGAN KURIKULUM ILMU-ILMU KEISLAMAN DI PTAI (Sebuah Ikhtiar Pencarian Landasan Filosofi) - Waryani Fajar Riyanto (Jurnal Forum Tarbiyah, 2013)
The endeavor to search philosophical foundation to develop the curriculum of Islamic sciences in the Islamic Religion College (PTAI) has been done. As the Ministry of National Education (MONE), for example, which has spawned a thematic-integrated curriculum model, it should have been by Ministry of Religious Affairs (MORA), PTAI, in this case, must also have the characteristic of integrative curriculum. The first and major step in the process to find the model, must be preceded by searching philosophical foundation, whether it uses one pillar, two pillars, three pillars, and so on? To find this philosophical foundation, the authors use 'model theory' on the relationship between religion and science, which is patterned into several types of models, namely: monadic (religion), dyadic (religion and science), triadic (religion, philosophy, and science), and so on. All three models are also identical with some kind of form of the Â relationship between science, namely: mono-disciplinary and intra-disciplinary (monadic); interdisciplinary and multidisciplinary (dyadic), as well as trans-disciplinary (triadic). As a result, one of the alternative philosophical foundation that can be used to develop the curriculum of Islamic sciences in PTAI is â€œtriadicâ€ model and it is a model of Integration-Interconnection Curriculum.